2019
DOI: 10.1101/832949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Background radiation impacts human longevity and cancer mortality: Reconsidering the linear no-threshold paradigm

Abstract: BACKGROUNDThe current linear-no-threshold paradigm assumes that any exposure to ionizing radiation carries some risk, thus every effort should be made to maintain the exposures as low as possible. Here, we examined whether background radiation impacts human longevity and cancer mortality. METHODSOur data covered the entire US population of the 3139 US counties, encompassing over 320 million people. The data on background radiation levels, the average of 5-year age-adjusted cancer mortality rates, and life expe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Actually, several previously published papers had noted such a lower cancer mortality rate in areas with higher background radiation level: this had been reported in some areas in India, Iran, and China and even previously in the US (David et al, 2021). So, those new epidemiological data do suggest that not only very low levels of radiation are not harmful, but that they could even be beneficial, possibly by reducing the cancer mortality rate (?…”
Section: New Epidemiological Data?mentioning
confidence: 84%
See 1 more Smart Citation
“…Actually, several previously published papers had noted such a lower cancer mortality rate in areas with higher background radiation level: this had been reported in some areas in India, Iran, and China and even previously in the US (David et al, 2021). So, those new epidemiological data do suggest that not only very low levels of radiation are not harmful, but that they could even be beneficial, possibly by reducing the cancer mortality rate (?…”
Section: New Epidemiological Data?mentioning
confidence: 84%
“…However a recent huge study covering the entire US population of the 3139 US counties and encompassing over 320 million people recently brought new data forcing us to reconsidered such a position (David et al, 2021). The authors show that life expectancy was approximately 2.5 years longer in people living in areas with a relatively high versus low background radiation, the difference being very significant (p < 0.005).…”
Section: New Epidemiological Data?mentioning
confidence: 99%
“…In fact, exposure to low radiation doses may induce trivial stress factors to enhance protective antioxidant pathways that may contribute to longevity [5,18]. It has recently been determined that background radiation within the natural range of low-dose radiation increases the life expectancy by approximately 2.5 years [92]. In support of this, others have shown that LDR is involved in DNA double-stranded-break repair mechanisms [33,93], which can ultimately delay cell death mechanisms.…”
Section: Discussionmentioning
confidence: 98%